2015
DOI: 10.1105/tpc.15.00214
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing of Arabidopsis abp1-5 Reveals Second-Site Mutations That May Affect Phenotypes

Abstract: Auxin regulates numerous aspects of plant growth and development. For many years, investigating roles for AUXIN BINDING PROTEIN1 (ABP1) in auxin response was impeded by the reported embryo lethality of mutants defective in ABP1. However, identification of a viable Arabidopsis thaliana TILLING mutant defective in the ABP1 auxin binding pocket (abp1-5) allowed inroads into understanding ABP1 function. During our own studies with abp1-5, we observed growth phenotypes segregating independently of the ABP1 lesion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Surprisingly, two null Arabidopsis abp1 mutants generated by the authors using ribozyme-based CRISPR and T-DNA insertion technologies do not show phenotype defects described in the case of other knockdown/knockout abp1 alleles. In addition, it has been demonstrated that phenotypes observed in the Arabidopsis abp1-1 and abp1-5 alleles might not be caused by the disruption of ABP1 Enders et al, 2015). These findings call into question the results of previous publications describing a prominent role of ABP1 in embryogenesis, growth, cell division, cell expansion, and auxin signaling [see Liu (2015) and Strader and Zhao (2016) for a commentary].…”
mentioning
confidence: 94%
“…Surprisingly, two null Arabidopsis abp1 mutants generated by the authors using ribozyme-based CRISPR and T-DNA insertion technologies do not show phenotype defects described in the case of other knockdown/knockout abp1 alleles. In addition, it has been demonstrated that phenotypes observed in the Arabidopsis abp1-1 and abp1-5 alleles might not be caused by the disruption of ABP1 Enders et al, 2015). These findings call into question the results of previous publications describing a prominent role of ABP1 in embryogenesis, growth, cell division, cell expansion, and auxin signaling [see Liu (2015) and Strader and Zhao (2016) for a commentary].…”
mentioning
confidence: 94%
“…This model, however, does not preclude a role for other factors that may be required for the auxin regulation of clathrin function during CME. Indeed, the recent finding that abp1 mutants show no gross growth defects (Enders et al, 2015;Gao et al, 2015) warrants further study of the role of ABP1 in the auxin-dependent regulation of CME. Recent studies showing that SA inhibition of plant CME is independent of SA receptor-mediated transcription (NONEXPRESSER OF PR GENES3/4; Du et al, 2013) support the SA inhibition of CME via an untranscriptional mechanism.…”
Section: Membrane Association and Function Of The Ap-2 Complex In Plamentioning
confidence: 99%
“…14,16 However, genuine null mutations in this gene have normal pavement cells, 19 and the abp1-5 line carries numerous additional mutations outside the ABP1 locus, obviously contributing to its phenotype. 20 Nevertheless, pavement cell lobing is also altered in auxin biosynthesis mutants (reviewed in ref. 14), and the ROP-dependent pathway, mediated by ICR1 and the exocyst complex subunit SEC3, acts at least in part through modulation of membrane trafficking, 12 which important not only for cell expansion (see ref.…”
mentioning
confidence: 99%
“…27 Intriguingly, the Arabidopsis abp1-5 line carries several mutations inactivating the FH17 gene, encoding a yet uncharacterized Class II formin. 20 It remains to be seen if this locus contributes to the abp1-5 pavement cell lobing defect that was originally attributed to impairment of auxin signaling.…”
mentioning
confidence: 99%